Amphibians in forest pools: Does habitat clustering affect community diversity and dynamics?. Issue 2 (2nd February 2017) - Van Dyke, Fred; Berthel, Allison; Harju, Seth M.; Lamb, Rachel L.; Thompson, Dan; Ryan, Julia; Pyne, Erin; Dreyer, Gwyneth
Abstract: Hydrologically isolated forest pools, both vernal and permanent, are receiving increased attention in conservation because they often provide fishless habitats for forest‐dwelling amphibians, reducing risk of predation to eggs and larvae. However, clarifying conservation value of such pools requires determination of whether the species they contribute to local biodiversity are unique or also present in other nearby wetlands such as freshwater marshes. We compared composition of amphibian communities in clustered pools to that of both spatially isolated pools and freshwater marshes in Illinois (USA) from 2008 to 2010 to determine (1) effects of clustering on community structure, species richness, and occupancy dynamics; (2) unique contributions of forest pools (six clustered and three isolated pools) to amphibian diversity compared to marshes ( n  = 6); and (3) species‐specific probabilities of occupancy by wetland type. Amphibian communities differed among wetland categories, with community similarity in the same year reduced 38% by differences between marshes, clustered pools, and isolated pools. Species richness was similar in clustered pools and marshes, but lower in isolated pools. Clustered pools contributed more species ( n  = 10) than marshes ( n  = 7) or isolated pools ( n  = 4). Anuran species had higher probability of greater relative abundance and salamanders had greater probability of encounter at clustered pools than at isolated pools, and probabilities of species‐specific site occupancy were lowest at isolated pools. Wildlife managers in Midwest USA can better understand species‐specific occupancy dynamics of amphibians in different wetland categories through this analysis and can optimize local amphibian species richness through conservation of clusters of forest pools.